f(x) = e^{-x} - e^{- 2·x}
f'(x) = 2·e^{- 2·x} - e^{-x}
f''(x) = e^{-x} - 4·e^{- 2·x}
F(x) = 0.5·e^{- 2·x} - e^{-x}
Nullstellen f(x) = 0
e^{-x} - e^{- 2·x} = 0 | z = e^{-x}
z - z^2 = 0
z(1 - z) = 0
z = 0 --> x = -ln(0) = keine Lösung
z = 1 --> x = -ln(1) = 0
Horizontale Tangenten f'(x) = 0
2·e^{- 2·x} - e^{-x} = 0 | Lösen wie vorher über Substitution
x = ln(2)
f(ln(2)) = 0.25
t(x) = 0.25
Wendepunkte f''(x) = 0
e^{-x} - 4·e^{- 2·x} = 0 | Auch hier wieder Lösen über Substitution
x = 2·ln(2)
f(2·ln(2)) = 3/16
WP(2·ln(2) | 3/16) = WP(1.386 | 0.1875)
lim x → -∞ f(x) = -∞
lim x → ∞ f(x) = 0
Fläche
F(∞) - F(0) = 0 - (-0.5) = 0.5
Skizze:
![](/?qa=blob&qa_blobid=13164477276924153874)